The control of commercial fraud - Leigh, L. H. (London : Heinemann, 1982)
This book is about the control of commercial fraud in Britain, primarily in England and Wales, through the medium of criminal process.
"Table of cases": p. [327]-333.
Includes index.
Includes bibliographical references: p. [315]-326.
osc 07/05/2018
Loans
Keywords: Commercial crimes; Fraud; Criminal law; Criminal justice, Administration of